Radiologic changes of long term foot insole use in symptomatic pediatric flatfoot. Issue 10 (10th March 2023) - Kim, Joon Yeop; Kim, Soo A; Kim, Yuntae; Hwang, Insu; Heo, Nam Hun
Abstract : Clinically, flatfoot, known as pes planus, is quite prevalent. It is classified into 2 types: flexible and rigid, both of which may or may not have symptoms. If a flexible flatfoot is symptomatic, it must be treated to prevent subsequent complications. In principle, most physicians initially use conservative methods, such as foot insoles. This study aimed to demonstrate the effect of long term use of a foot insole using plain radiography as an objective measurement in children with symptomatic flexible flatfoot (SFFF) in large samples. This study analyzed the medical records of 292 children aged < 18 years who were diagnosed with SFFF. Of these, 200 children (62 boys and 138 girls, mean age: 6.49 ± 2.96 years) were selected and conservatively treated with foot insoles. They were periodically followed up within 3 to 4 months to modify the foot insole and perform radiologic evaluations, such as foot radiography. The calcaneal pitch angle (CPA) and talo first metatarsal angle were measured and compared individually using foot lateral radiographs, which were pictured in a bilateral barefoot state. The treatment was terminated by repeating the same procedure until the symptoms disappeared. A significant improvement ( P < .001) was observed in the radiological indicators, both CPA and talo first metatarsal angle, regardless of age, after the application of soft foot insoles. However, the right foot CPA in the group with valgus deformity was an exception ( P = .078). This study showed that in children diagnosed with SFFF under 18 years of age, wearing a periodically revised foot insole as conservative treatment could not only decrease the symptoms, but also improve the radiologic indices.